A103 COMBINATORIAL EFFECT OF EARLY LIFE ANTIBIOTIC EXPOSURE AND HIGH-FAT DIET ON COLITIS SUSCEPTIBILITY. (15th March 2019) - Marshall, K; Goethel, A; Croitoru, K
Abstract: Background: The etiology of Inflammatory Bowel Disease (IBD) is multifactorial, involving genetics, the immune response, environment and the gut microbiota. Early life antibiotic exposure and a high-fat 'Western' diet have both been linked to increased risk of IBD. Aims: We hypothesized that genetically susceptible Nod2 -deficient mice that received a 'double hit' of early life antibiotics and high-fat diet (HFD) throughout life would be more susceptible to colitis. Methods: Following birth, Nod2 -/ - mice were given amoxicillin-supplemented or control water until weaning (day 21). At weaning, mice received either normal diet (ND, 18% kcal from fat) or HFD (45% kcal from fat, Envigo). Stool samples and weights were collected weekly starting at weaning. On days 56–61, 3.5% DSS was administered to induce colitis. Mice were sacrificed and tissues harvested for analysis on day 64. Results: At weaning, mice treated with amoxicillin weighed more than water-treated mice. Water + HFD mice displayed a trend for increased weight gain over time compared to all other groups. As expected, from days 56–61, mice treated with DSS lost weight, however, mice on HFD lost significantly less weight than ND mice. DSS treatment resulted in shortened colon length, but no difference was seen between HFD and ND treatment groups. Interestingly, amoxicillin + HFD treatment resulted in significantly higher fat pad weight than other treatment groups, and while DSS resulted in reduction of fat pad weight, amoxicillin + HFD mice had significantly more fat pad remaining than other DSS treatment groups. Fecal lipocalin-2 (Lcn-2) did not differ between groups at day 56, before colitis induction. Increased Lcn-2 levels were observed in DSS-treated mice, and amoxicillin + HFD mice had increased Lcn-2 compared to water + HFD and amoxicillin + ND mice on day 64. Conclusions: While water + HFD mice displayed greater weight gain trends overall, amoxicillin + HFD mice had greater fat pad weights, in both DSS and non-DSS groups. In contrast to what was hypothesized, HFD prevented dramatic weight changes upon DSS administration. Fecal Lcn-2 levels were increased in amoxicillin + HFD mice following DSS, suggesting that while weight change was reduced, these mice were still experiencing significant inflammation. Together, this indicates that a combination of HFD and early life antibiotics could lead to alterations of the gut microbiota and influence severity of DSS. Analysis of the microbiota in these mice is currently underway. These data reinforce the hypothesis that various environmental factors can have combinatorial effects on colitis susceptibility, possibly via gut microbiota manipulation. This work was supported by a CAG Summer Studentship Award. Funding Agencies: CAG